Anterior cruciate ligament injury prevention in sport: biomechanically informed approaches - Weir, G. (Sports Biomechanics, 2021)
This paper reviews a series of studies contributing to a framework for preventing anterior cruciate ligament (ACL) injuries in sport. As the majority of these injuries are non-contact in nature, theoretically, these injuries are preventable. The studies presented in this paper focus on understanding biomechanical countermeasures of ACL injury and how this knowledge can inform both screening and training intervention research and practice in sport. These countermeasures include: 1) modifying an athlete`s technique to reduce externally applied loads to the knee; 2) increasing the muscle support around the knee and hip to counter elevated loads applied to the knee and; 3) improving an athlete`s perception during dynamic sports tasks to increase planning time to coordinate desirable movement patterns. By furthering the empirical evidence of modifiable biomechanical countermeasures of ACL injury risk, we can better understand best practices for developing interventions on a mass scale to prevent ACL injuries in the sporting community.